Conversion of Conventional Bank Into Sharia Bank in Maqashid Sharia Perpective - Fajri, Desmal (Muhammadiyah Law Review Journal, 2024)
Maqashid al-syariah is a number of good goals that Islamic sharia wants to achieve by allowing or prohibiting something. This research aims to analyze the benefits of converting a conventional bank operational system to a sharia bank from a sharia maqasid perspective. This research uses a type of library research and is qualitative in nature. Then the research data was analyzed descriptively-qualitatively in order to obtain a complete picture of the problems studied. The research results show that the urgency of converting conventional banks to sharia banks is because a number of ulama believe that interest is the same as usury and is haram, so Muslims must die. The benefits of converting a conventional bank into a sharia bank are in order to realize the maqashid of sharia, namely maintenance, religion, soul, mind, property and descendants.